If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 1 + 5x = 13 + 8x Reorder the terms: 1 + 5x + 5x = 13 + 8x Combine like terms: 5x + 5x = 10x 1 + 10x = 13 + 8x Solving 1 + 10x = 13 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 1 + 10x + -8x = 13 + 8x + -8x Combine like terms: 10x + -8x = 2x 1 + 2x = 13 + 8x + -8x Combine like terms: 8x + -8x = 0 1 + 2x = 13 + 0 1 + 2x = 13 Add '-1' to each side of the equation. 1 + -1 + 2x = 13 + -1 Combine like terms: 1 + -1 = 0 0 + 2x = 13 + -1 2x = 13 + -1 Combine like terms: 13 + -1 = 12 2x = 12 Divide each side by '2'. x = 6 Simplifying x = 6
| 6p=55 | | 2(-3x+7)+4x-3=5-4(2x+9)+1 | | x-4=12+1-x-1 | | 5=4n+15 | | 7x+18x-8=5(5x+4) | | 5m+4(5m-9)=-5(3-5m) | | 4+1+8k-4k=k-1 | | [(X)(x)]-10x=-21 | | 1/12x+3=1/4x-5 | | -8-3w=5w+10+6 | | A+.5=q | | 2x-3=0.6+3 | | -6-5n+4-n=-8n+4 | | 250=8x+x | | 6+4x=-12-2x | | 2(2x+3)=9x+1-5x+5 | | 47-16+8y=-4 | | 2(5c+2)-2c=3(2c+3)+7c | | 7n-1=6n-6+4+6 | | -10w+5-w=17 | | -4(-2x+6)+10=4x+3(5x-1) | | -4(-2x+6)+10=4x+3x(5x-1) | | 6x-6-4x+24=4x+8 | | -18=m+5 | | -2x+6y=34 | | 5x-3(x+2)=5x-6 | | x*tanh(ax)=b | | [(X-12)(x-12)]=36 | | (-2,11)m=4/3 | | m=fw | | 15xp-10py+21xq-14qy= | | x+x+1x+2=51 |